Capability as a Yardstick for Flexicurity Using the Senian Paradigm to Evaluate a European Policy Agenda - Lehweß-Litzmann, René (Universitätsverlag Göttingen, 2014)
Flexicurity is a European policy agenda seeking to increase both flexibility and security in the labour-market. This book argues that it needs a revision: Although flexicurity is set out to change the way Europeans work and live, and even though it is being justified by workers' needs, flexicurity lacks of a clear and democratically justified vision of society. Flexicurity is confronted here with Amartya Sen's capability-approach, a paradigm of well-being evaluation. How is flexicurity related to a concept of employment as part of a way of life which people have reason to value? How capability-friendly are established flexicurity-indicators? It is thus shown how the capability-approach can be used in the field of labour-market and social policy.